Modelling the anisotropic thermal conductivity of 3D logpile structures. Issue 10 (August 2023) - Moreno-Sanabria, L.; Barea, R.; Osendi, M.I.; Belmonte, M.; Miranzo, P.
Abstract: Assessing and predicting the thermal conductivity (κ) of macroporous materials is particularly important for additive manufactured 3D structures, as they offer considerable potential for tuning architectures and properties. In this work, finite element methods (FEM) are used to simulate the transient plane source test in 3D logpile lattices, approaching the effect of interfacial thermal contact resistances on κ measurement. Besides, the influence of different geometrical parameters (rod diameter, macropore size and overlapping between rods in consecutive layers) and the κ of the strut material on the anisotropic thermal conductivity of 3D lattices are investigated. The models are validated using experimental data for 3D composite structures of γ-Al2 O3 with graphene nanoplatelet contents up to 18 vol%, as well as with reported data for alike scaffolds, all printed by robocasting. Results have strong impact for the application of novel 3D structures in energy production and storage, catalysis and heat transfer-related fields. Highlights: FEM is a powerful tool for simulating thermal behaviour in additive manufactured porous structures. The feasibility of TPS for measuring κ of 3D lattices is proved by fitting experimental data. Anisotropic thermal conduction of logpile structures depends on a fine balance between cell design and κ strut.